A holistic strategic perspective of football industry stakeholders. (4th November 2022) - Yiapanas, George; Thrassou, Alkis; Vrontis, Demetris
Football clubs strive to remain competitive and sustainable in a multi-faceted industry which involves a plethora of stakeholders. Consequently, it is imperative to comprehend the industry structures, identify the stakeholders, and implement processes to manage every relationship. Although numerous studies have applied stakeholder theory in the specific field, they tend to focus on stakeholders as broad categories, overlooking the fact that various sub-categories exist as diverse entities. The aim of this study is to identify every football industry stakeholder and develop a strategic stakeholder framework from the club perspective. Methodologically the research relies on an extensive theoretical examination of stakeholder theory, through the explication and evaluation of its development over the last 40 years. The findings enhance the theory itself in a context that until now was in its infancy and provide solid foundations to practitioners to delineate the synergies and implement principles on how to constructively manage these relationships.